School operational experience integrating children’s training with special educational needs - Ostanina, Nadiežda Vladimirovna (Lietuvos matematikos rinkinys, 2008)
In this article operational experience of school psychological service in organizing pedagogical support to the pupils with special educational needs is described. The system of pedagogical support is directed on realization of an idea of integrated and differentiated training for children with a delay in mental development at a comprehensive school. Difficulties of training for children with infringement development of separate cognitive functions (an example of studying mathematics) and forms of individual help to them at a lesson within the limits of modified (adapted) program are described.